The ethical ambivalence of resistant violence: notes from postcolonial south Asia - Roy, Srila (Palgrave Macmillan, 2009)
In the face of mounting militarism in south Asia, this essay turns to anti-state, ‘liberatory’ movements in the region that employ violence to achieve their political aims. It explores some of the ethical quandaries that arise from the embrace of such violence, particularly for feminists for whom political violence and militarism is today a moot point. Feminist responses towards resistant political violence have, however, been less straightforward than towards the violence of the state, suggesting a more ambivalent ethical position towards the former than the latter. The nature of this ambivalence can be located in a postcolonial feminist ethics that is conceptually committed to the use of political violence in certain, albeit exceptional circumstances on the basis of the ethical ends that this violence (as opposed to other oppressive violence) serves. In opening up this ethical ambivalence – or the ethics of ambiguity, as Simone de Beauvoir says – to interrogation and reflection, I underscore the difficulties involved in ethically discriminating between forms of violence, especially when we consider the manner in which such distinctions rely on and reproduce gendered modes of power. This raises particular problems for current feminist appraisals of resistant political violence as an expression of women's empowerment and ‘agency’.